PENERAPAN TEKNIK ICEBREAKER UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN LARUTAN ASAM BASA DI KELAS XI IPA SMAN 9 PEKANBARU - Esa Oktafiyanti Gea; Herdini '; Maria Erna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research on the implementation tecnic Icebreaker has been done to know improve student’s achievement and classified to what category of student’s achievement on the subject of acid and base solution in class XI science of SMAN 9 Pekanbaru. Form of experiment research used pretest-posttest design. The sample consisted of two classes, XI IPA 2 as experiment class and XI IPA 1 as control class that randomly selected after testing normality and homogeneity. Experiment class was treated with implementing technique Icebreaker and the control class was treated without icebreaker technique. The data in this research obtained from pretest and posttest. Analysis of data used t-test. Data of research obtained tcount > ttable (3,14 > 1,67) It means that using tecnic Icebreaker can improve student’s achievement on the subject of acid and base solution in class XI Science of SMAN 9 Pekanbaru. The category improvement of student’s achievement in experiment class was high category ( N-Gain = 0,85) and in control class was medium category (N-Gain =0,69).Keyword : learning, Icebreaker, learning achievement, acid and base solution